DISTRIBUTION OF SETTLEMENTS AND COMMERCIAL AREAS ALONG ZARIA – SOKOTO HIGHWAY, NIGERIA - Akhadelor, Muhammad Oyale (FUDMA JOURNAL OF SCIENCES, 2023)
This study examined the pattern of distribution of Settlement and Commercial areas along Zaria – Sokoto Highway, Nigeria. Primary and secondary sources were used to elicit for information from respondents using questionnaire and direct field observation using the purposive sampling method to administered 300 copies of questionnaire in the survey settlements and commercial areas. Descriptive and inferential statistics were used to analyse the information. The study revealed that 38% of the respondents are engage in farming activities. Results also showed that 52% of the respondents had migrated alone to Zaria – Sokoto highway. Sixty – eight percent (68%) of the settlements grew as a result of road maintenance of the 400km Zaria – Sokoto highway around point where facilities and activities like markets, road junction, trading and commercial areas were located The main reasons for expansion of these settlements along the highway includes natural population increase, migration, increasing social activities and commerce. The result revealed that Settlements and commercial areas pattern of distribution are linear. The P – value is less than 0.05, which implies that there is significant differences on the role of road maintenance and rehabilitation on commercial activities and growth of settlement in North Western part of Nigeria. It was therefore recommended that social welfare facilities and more security should be provided to enhance quality of live and protect properties of people along Zaria - Sokoto highway.